Making the blindsighted see. - Silvanto, J; Cowey, A; Lavie, N; Walsh, V (2007)
A lesion of striate cortex, area V1, produces blindness in the retinotopically corresponding part of the visual field, although in some cases visual abilities in the blind field remain that are paradoxically devoid of conscious visual percepts ("blindsight"). Here we demonstrate that the blindsight subject GY can experience visual sensations of phosphenes in his blind field induced by transcranial magnetic stimulation (TMS). Such blind field percepts could only be induced when stimulation was applied bilaterally, i.e. over GY's area V5/MT in both hemispheres. Consistent with an earlier report [Cowey, A., and Walsh, V. (2000). Magnetically induced phosphenes in sighted, blind and blindsighted observers. Neuroreport, 11, 3269-3273], GY never experienced phosphenes when stimulation was restricted to his ipsilesional V5/MT. To the best of our knowledge this is the first time GY has experienced visual qualia in his blind hemifield. The present report characterizes the necessary conditions for such conscious experience in his hemianopic visual field and interprets them as demonstrating that only via a contribution from GY's intact hemisphere can activation in the damaged hemisphere reach visual awareness.